(untitled) (Homiletic, 2024)
Dr. Sabrina Müller advocates nurturing diversity in preaching by integrating feminist and cultural insights into the field of homiletics. In response, this paper compares her research to another study on feminism, emphasizing that gender and culture encompass more than just sex and race. Further, this paper attributes the stagnancy of the preaching ministry within the Catholic Church in South Korea to a lack of motivation to adapt to changing times and a tendency to rest on the laurels of past triumphs, particularly in the realm of modern democratic history. To address the issue, embracing the Synodality of the Catholic Church, which aligns with Dr. Müller’s focus on diversity in the preaching ministry, is imperative. This approach offers a remedy for the church to overcome the monotonous tendencies of clericalism and the gender-discriminatory practices influenced by Confucianism.